The Licensing Transformation in Small and Medium Industries Affecting Environment Following the Establishment of the Law on Job Creation: A Case Study of the Washing Industry in Bandung Regency - Adikancana, Santi Hapsari Dewi; Santosa, Mas Achmad (Faculty of Law, Universitas Padjadjaran, 2024)
The Law on Job Creation and its derivative regulations have shifted the licensing paradigm from a license-based approach to a risk-based one, focusing its primary consideration on risk. The Government Regulation Number 5 of 2021 on the Implementation of Risk-Based Business Licensing regulates the division of risks into four types: low, medium-low, medium-high, and high. The purpose of the Law on Job Creation is to provide ease of doing business. Unfortunately, business certainty has not been fully achieved due to various difficulties. This study aims to describe (1) the industrial conditions in Bandung Regency, especially in the washing industry, on the small and medium scales, and (2) the regulations of small and medium industries whose business activities have the potential to cause pollution. This study concludes that Industrial regulation in small and medium-sized enterprises requires collaborative governance between the government, business actors, and the community. Consistent law enforcement and penalties for violations are essential so that business activity continues to increase and the environment remains sustainable.